From England to Bohemia heresy and communication in the later Middle Ages - Van Dussen, Michael, 1977- (Cambridge ; New York : Cambridge University Press, 2012)
"This is the first book-length study of the influential cultural and religious exchanges which took place between England and Bohemia following Richard II's marriage to Anne of Bohemia in 1382. The ensuing growth in communication between the two kingdoms initially enabled new ideas of religion to flourish in both countries but eventually led the English authorities to suppress heresy. This exciting project has been made possible by the discovery of new manuscripts after the opening up of Czech archives over the past twenty years. It is the only study to analyze the Lollard-Hussite exchange with an eye to the new opportunities for international travel and correspondence to which the Great Schism gave rise, and examines how the use of propaganda and The Council of Constance brought an end to this communication by securing the condemnation of heretics such as John Wyclif"--
"When Anne Hudson published The Premature Reformation (1988BIB-209), little did she know how timely her call for further study of Lollard-Hussite communication would prove to be. For the very next year, the Velvet Revolution in Czechoslovakia, followed by the removal of Cold War-era boundaries, would open up new possibilities for communication between Anglophone and Slavic scholars, renewing access to archives that outsiders previously could consult only with difficulty"--
Machine generated contents note: Introduction: beyond reformist historiography: communication in schism Europe; 1. 'The occasion of Queene Anne'; 2. Common ground: Richard Rolle at the edges of orthodoxy in England and Bohemia; 3. Conveying heresy: texts, tidings and the formation of a Lollard-Hussite fellowship; 4. 'Ad regna et loca extranea': diplomacy against heresy, 1411-1416; 5. The aftermath: Bohemia in English religious polemic before Foxe; Afterward; Appendix A. Three verse eulogies of Anne of Bohemia: an edition; Appendix B. News of the Oldcastle Rising, 1414: an edition.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Reformation -- Early movements; Church history -- Middle Ages, 600-1500.; England -- Church history -- 1066-1485.; Bohemia (Czech Republic) -- Church history; Lollards; Hussites; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; RELIGION / Christianity / History; Electronic books